2017
DOI: 10.5897/ajar2016.12028
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of Ixodid tick species infesting cattle reared under traditional farming systems in Tanzania

Abstract: Ticks and tick-borne diseases are serious constraints to livestock production in Tanzania and other sub-Saharan African countries. Despite this, knowledge on the abundan ce of tick species infesting cattle in most parts of Tanzania is insufficient or lacking. This study was conducted to identify species and establish the abundance of ticks infesting cattle in Mara, Singida and Mbeya regions of Tanzania. The ticks were collected from one side of the body, counted and identified, based on morphological character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
3
10
2
Order By: Relevance
“…The low cattle density recorded across the expansive extension areas of the study area and the probable low susceptibility of indigenous cattle to tick infestation, in the face of other alternative reservoir species that includes wildlife for multi-host tick species, may have been the host factors that resulted in the dissociation between tick count and cattle stocking density (48). Age was not a suitable predictor of ticks in our study even though it has previously been found to be elsewhere by others (49). This may be attributed to the non-representativeness of age in our study in that cattle brought for slaughter are mainly adults of a certain age category as the price at the abattoir is based solely on weight and hence not representative of the source population age ranges.…”
Section: Effect Of Host Factors On Tick Abundance and Distributioncontrasting
confidence: 53%
“…The low cattle density recorded across the expansive extension areas of the study area and the probable low susceptibility of indigenous cattle to tick infestation, in the face of other alternative reservoir species that includes wildlife for multi-host tick species, may have been the host factors that resulted in the dissociation between tick count and cattle stocking density (48). Age was not a suitable predictor of ticks in our study even though it has previously been found to be elsewhere by others (49). This may be attributed to the non-representativeness of age in our study in that cattle brought for slaughter are mainly adults of a certain age category as the price at the abattoir is based solely on weight and hence not representative of the source population age ranges.…”
Section: Effect Of Host Factors On Tick Abundance and Distributioncontrasting
confidence: 53%
“…Other high risk areas include those located in low altitudes, experiencing high precipitation and bimodal rainfall, being proximal to forests and having contacts with wild animals, which are characteristic features of north-eastern, southern-highland and Lake zones of the country (Sindato et al, 2014;. Although there is limited data on tick's distribution in Tanzania, available information suggests that they are widely distributed in different ecological zones of the country (Swai et al, 2005;Kwak et al, 2014;Kerario et al, 2017). Individuals encroaching to forest areas for different activities including hunting and timbering are likely to be exposed to preparation and consumption of bush meat or handling of dead primates, and/ or residing in areas that border high-disease risk areas are considered to be at an increased risk for EVD (Bannister, 2010;Feldmann & Geisbert, 2011).…”
Section: Study Areas and Designmentioning
confidence: 99%
“…Ticks are one of the most important arthropod vectors and reservoirs for a wide variety of pathogenic agents such as viruses, bacteria, and protozoa which can cause diseases in human, livestock and wild animals [ 1 ]. Ticks transmit diseases that leads to extensive economic loses to resource-poor farming communities especially in tropical and subtropical regions where almost 80% of the world’s cattle population is reared [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The grazing land for the animals is no longer sufficient due to increased number of cattle, other domestic animals, and human populations. Most of the indigenous cattle are thus widely grazed in grasslands and woodlands and hence exposed to high risk of tick infestation [ 1 , 7 ]. The climatic condition of Tanzania is greatly favoring the development and survival of several tick species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation